Genomic survey of TCP transcription factors in plants: Phylogenomics, evolution and their biology - Zhou, Haiying; Hwarari, Delight; Ma, Hongyu; Xu, Haibin; Yang, Liming; Luo, Yuming (Frontiers in Genetics, 2022)
The TEOSINTE BRANCHED1 (TBI1), CYCLOIDEA (CYC), and PROLIFERATING CELL NUCLEAR ANTIGEN FACTORS (PCF1 and PCF2) proteins truncated as TCP transcription factors carry conserved basic-helix-loop-helix (bHLH) structure, related to DNA binding functions. Evolutionary history of the TCP genes has shown their presence in early land plants. In this paper, we performed a comparative discussion on the current knowledge of the TCP Transcription Factors in lower and higher plants, their evolutionary historybased on the phylogenetics of849 TCP proteins from 37 plant species, duplication events and biochemical roles in some of the plants species. Phylogenetics investigations confirmed the classification of TCP TFs into Class I (the PCF1/2), and Class II (the C- clade) factors; the Class II factors were further divided into the CIN- and CYC/TB1- subclade. A trace in the evolution of the TCP Factors revealed an absence of the CYC/TB1subclade in lower plants, and an independent evolution of the CYC/TB1subclade in both eudicot and monocot species.54%of the total duplication events analyzed was biased towards the dispersed duplication, and we concluded that dispersed duplication events contributed to the expansion of the TCP gene family. An analysis in the TCP factor functional roles confirmed their involvement in various biochemical processes which mainly included promoting cell proliferation in leaves in Class I TCPs, and cell division during plant development in Class II TCP Factors. Apart from growth and development, the TCP Factors were also shown to regulate hormonal and stress response pathways. Although this paper does not exhaust the present knowledge of the TCP Transcription Factors, it provides a base for further exploration of the gene family.